A quality assessment of systematic reviews on telerehabilitation: what does the evidence tell us? - Marco Rogante; Dahlia Kairy; Claudia Giacomozzi; Mauro Grigioni (Istituto Superiore di Sanità, 2015)
Aims. To evaluate the quality of systematic reviews on telerehabilitation. Methods. The AMSTAR - Assessment of Multiple Systematic Reviews - checklist was used to appraise the evidence related to the systematic reviews. Results. Among the 477 records initially identified, 10 systematic reviews matched the inclusion criteria. Fifty percent were of high quality; anyway the majority of them did not report the following aspects: i) analysis of the grey literature; ii) a list of the excluded studies and their characteristics; iii) the identification of possible source of bias and the assessment of its likehood; iv) an appropriate method to combine the findings of the included studies addressing the heterogeneity as well. From the main findings of the high-scored systematic reviews telerehabilitation resulted at least as effective as usual care: 1) in the short term treatment of mental health related to people affected by spinal cord injury; 2) in rural communities for treating patients affected by chronic conditions; 3) in treating common pathologies (mainly asthma) affecting children and adolescents. As for stroke, evidence is currently insufficient to reach conclusions about its effectiveness. As for costs, there is insufficient evidence to confirm that telerehabilitation is a cost-saving or cost-effective solution. Conclusions. In the authors' knowledge this is the first attempt to evaluate the quality of systematic reviews on telerehabilitation. This work also identified the main findings related to the high-scored systematic reviews; the analysis confirms that there is a mounting evidence concerning the effectiveness of telerehabilitation, at least for some pathologies.